Temporary international migration, shocks and informal finance: Analysis using panel data - Tanika Chakraborty; Manish Pandey (IZA Journal of Development and Migration, 2022)
We examine households' temporary international migration response when faced with shocks in rural Kyrgyzstan. Using a household fixed effects model, we find that while a drought shock increases migration, a winter shock reduces migration. We argue that this difference is because of the trade-off between two effects of a shock for a household: loss of income and increase in the need for labor services. Migration increases when the former effect of a shock dominates and it reduces when the latter effect dominates. We explore these mechanisms further, and find that when households have easier access to informal finance the migration response is muted only for shocks for which the adverse income effect dominates. These findings provide evidence in favor of our proposed mechanisms through which shocks affect migration.
Keywords: J61; O15; O16; 330; temporary migration; shocks; insurance; informal finance; Asia; Kyrgyzstan